1999
DOI: 10.1161/01.res.85.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Copper-Zinc Superoxide Dismutase Induces Cell Growth, Hypertrophic Phenotype, and Apoptosis in Neonatal Rat Cardiac Myocytes In Vitro

Abstract: Oxidative stress has been implicated in the pathophysiology of myocardial failure. We tested the hypothesis that inhibition of endogenous antioxidant enzymes can regulate the phenotype of cardiac myocytes. Neonatal rat ventricular myocytes in vitro were exposed to diethyldithiocarbamic acid (DDC), an inhibitor of cytosolic (Cu, Zn) and extracellular superoxide dismutase (SOD). DDC inhibited SOD activity and increased intracellular superoxide in a concentration-dependent manner. A low concentration (1 micromol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(155 citation statements)
references
References 26 publications
4
147
0
4
Order By: Relevance
“…8). DDC inhibition of superoxide dismutase has been shown to increase superoxide generation in neonatal rat cardiac myocytes (24), and we demonstrated that the caspase-3-like activity of both oleate-and palmitate-incubated cells increased in the presence of increasing concentrations of DDC (Table 2). However, the caspase-3-like activity of oleate-treated cells in the presence of DDC, even at a concentration (100 M) previously shown to induce apoptosis (24), never attained the levels achieved by palmitate incubation alone (without DDC).…”
Section: Nf-b Binding Activity and Effect Of Superoxide Dismutase Inhmentioning
confidence: 53%
“…8). DDC inhibition of superoxide dismutase has been shown to increase superoxide generation in neonatal rat cardiac myocytes (24), and we demonstrated that the caspase-3-like activity of both oleate-and palmitate-incubated cells increased in the presence of increasing concentrations of DDC (Table 2). However, the caspase-3-like activity of oleate-treated cells in the presence of DDC, even at a concentration (100 M) previously shown to induce apoptosis (24), never attained the levels achieved by palmitate incubation alone (without DDC).…”
Section: Nf-b Binding Activity and Effect Of Superoxide Dismutase Inhmentioning
confidence: 53%
“…[2][3][4][5][6][7][8][9] Experimental studies have shown the beneficial effects of antioxidants for prevention of heart failure. 5,14,32 However, the effectiveness of antioxidants for human patients with heart failure has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Furthermore, we and other investigators have reported that ROS have important functions in apoptosis and cytokine-stimulated hypertrophy of cardiac myocytes. 4,5 Clinical studies have also revealed that lipid peroxides and 8-iso-prostaglandin F2␣, which are the major biochemical products of ROS generation, are elevated in plasma and pericardial fluid of patients with heart failure. 6 -9 However, direct evidence of oxidative stress elevation in the human myocardium has not been obtained.…”
mentioning
confidence: 99%
“…12,17 Furthermore, other reports have shown that loss of SOD can initiate apoptosis in some cell types, 29 therefore we hypothesized that diminished SOD in airway epithelial cells might be a central event mediating airway epithelial cell apoptosis. To address whether inactivation of SOD and/or increasing reactive oxygen species play a role in airway apoptosis, we treated BET1A cells with pyrogallol, a superoxide-producing agent, 2-ME, a SOD activity inhibitor or hydrogen peroxide, in a dose-and time-dependent manner.…”
Section: Effects Of Oxidative Stress On Airway Epithelial Cellsmentioning
confidence: 96%